Encapsulation and Controlled Release of Resveratrol Within Functionalized Mesoporous Silica Nanoparticles for Prostate Cancer Therapy - Chaudhary, Zanib; Subramaniam, Sugarniya; Khan, Gul Majid; Abeer, Muhammad Mustafa; Qu, Zhi; Janjua, Taskeen; Kumeria, Tushar; Batra, Jyotsna; Popat, Amirali (Frontiers in Bioengineering and Biotechnology, 2019)
Resveratrol (RES) is a naturally existing polyphenol which exhibits anti-oxidant, anti-inflammatory and anti-cancer properties. In recent years, RES has attracted attention for its synergistic effect with other anti-cancer drugs for the treatment of drug resistant cancers. However, RES faces the issues of poor pharmacokinetics, stability and low solubility which limits its clinical application. In present study, RES has been loaded onto uniformly sized ( 60 nm) mesoporous silica nanoparticles (MSNs) to improve its in-vitro anti-proliferative activity and sensitization of Docatexal in hypoxia induced drug resistance in prostate cancer. RES was efficiently encapsulated within phosphonate (negatively charged) and amine (positively charged) modified MSNs. The effect of surface functionalisation was studied on the loading, in vitro release, anti-proliferative and cytotoxic potential of RES using prostate cancer cell lines. PO3-MSNs showed slower in vitro release of RES at pH 7.4 whereas NH2-MSNs did not show any significant change in release at pH 7.4 compared with free RES. At pH 5.5, however, both the PO3-MSNs and NH2-MSNs showed significant control over release (around 40 % less release compared with free RES in 24 hours). Phosphonate modified MSNs significantly enhanced the anti-proliferative potential of RES with an IC50 of 7.15 µM as compared to 14.86 µM of free RES whereas amine modified MSNs didn’t affect proliferation with an IC50 value higher than free RES (20.45 µM). Furthermore, RES loaded onto PO3-MSNs showed robust and dose dependent sensitization of Docatexal in hypoxic cell environment which was comparable to pure RES solution. This study provides an example of applicability of MSNs loaded with polyphenols such as RES as next generation anticancer formulations for treating drug resistant cancers such as prostate cancer.